Exploring Human Misuse and Abuse of Veterinary Drugs: A Descriptive Pharmacovigilance Analysis Utilising the Food and Drug Administration’s Adverse Events Reporting System (FAERS) - JOSIE DUNN (Toxics, 2024)
Introduction: Evidence suggests an increasing misuse of veterinary medicines by humans.This study aims to analyse Adverse Events (AEs) associated with selected veterinary productsusing the Food and Drug Administration Adverse Events Reporting System (FAERS). Methods: Adescriptive pharmacovigilance analysis was conducted on AEs related to 21 drugs approved forhuman and/or animal use. Results: A total of 38,756 AEs, including 9566 fatalities, were identified.The United States reported the highest number of cases (13,532), followed by Canada (2869) andthe United Kingdom (1400). Among the eight drugs licenced exclusively for animals, levamisole,pentobarbital, and xylazine were most frequently reported. Reports predominantly involved males(57%) from the 18–64 age group, with incidents related mainly to overdose, dependence, and multiagent toxicities. Unmasking techniques revealed ‘intentional overdose’ as the primary reaction.Polysubstance use was evident in 90% of the drugs, with benzodiazepines/Z-drugs and opioids ascommon co-used classes. Conclusions: Veterinary medications are increasingly infiltrating the illicitdrug market due to their pharmacological properties. This trend highlights the need for heightenedvigilance and awareness to prevent further public health risks associated with the adulteration ofillicit substances with veterinary products like xylazine and pentobarbital.